Engineering Single-Atom Catalysts on Conjugated Porphyrin Polymer Photocatalysts via E-Waste for Sustainable Photocatalysis - Bayarkhuu, Bolormaa; Cho, Hyekyung; Cho, Gaeun; Hong, Jeeho; Hong, Yeongran; Baek, Se-Woong; Yang, Sungeun; Yavuz, Cafer T.; Kim, Han Seul; Byun, Jeehye (John Wiley & Sons Ltd., 2025)
This study presents a surface engineering strategy utilizing electronic waste (e-waste) to incorporate single-atom catalysts on conjugated polymers. Employing a conjugated porphyrin polymeric photocatalyst, gold single-atom-site catalysts are successfully introduced using the acidic metal leachates from e-waste, where metal speciation and composition are regulated during the metal loading processes. The resulting photocatalyst with gold single atoms demonstrates a remarkable hydrogen peroxide (H2O2) selectivity of up to 97.56%, yielding a pure H2O2 solution at 73.3 µm h−1 under white LED illumination. The produced H2O2 is activated to •OH radicals on the same polymer with mixed gold and iron atoms, enabling a photo-Fenton reaction and the complete degradation of toxic microcystin-LR within 10 min under visible light. This study highlights the universal applicability of the metal mining strategy in various photoreactions. It is believed that this discovery pioneers sustainable photocatalysis, allowing the tuning of reactivity and selectivity on photocatalytic surfaces using metal waste.